The banquet of the brethren: an Ismaili guide to spiritual hermeneutics ; part 1 a Persian critical edition of Nasir-i Khusraw's 'Khwan al-ikhwan' - Nāṣir Ḫusrau 1004-1078 (I.B. Tauris, 2024)
"The Ismaili missionary and poet, Nasir-i Khusraw (d. after 1070), wroteKhwan al-ikhwan(The Banquet of the Brethren) when he was living in his remote mountain refuge of Yumgan in Badakhshan.A work of philosophical theology, it consists of a sequence of dynamic arguments for divine unicity (tawhid), the authority of the Prophet Muhammad, his legatee, 'Ali b. Abi Talib, and his descendants, the imams from the line of Isma'il b. Ja'far al-Sadiq. This new edition is based on two extant manuscripts of Khwan al-ikhwan making it a more comprehensive resource. Written in Persian,Khwan al-ikhwanincludes a precis of ideas found in a work by an earlier missionary, Abu Ya'qub al-Sijistani (d. ca. 971), the Kitab al-Yanabi', which Nasir-i Khusraw recast and then extended in 100 chapters. The current publication consists of a new Persian critical edition of the text, with an introduction that discussesKhwan al-ikhwanin the context of both Nasir-i Khusraw’s other works and al-Sijistani’s Kitab al-Yanabi, in addition to notes throughout. The book is an important example of Ismaili theology and a reflection of the learning of the age including the conception of a geo-centric cosmos, Aristotelian physics, and Neoplatonic philosophy, which greatly influenced the Ismaili missionaries (orda'is) of the Iranian lands. The editorial apparatus in this edition bringsKhwan al-ikhwanto an even wider readership advancing the field of Ismaili Studies."
Keywords: Nāṣir-i Khusraw / 1004-approximately 1088; Ismailites / Hermeneutics; Ismailites / Doctrines; Islam / Early works to 1800